2016
DOI: 10.1097/ncc.0000000000000258
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Experiences of Siblings of Children With Cancer

Abstract: The findings of this review provide evidence to help health professionals to assess the needs of the siblings to enhance their sense of self within the family. Providing the siblings with suitable resources should result in better adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
92
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(99 citation statements)
references
References 22 publications
4
92
0
3
Order By: Relevance
“…As treatment continued for the child with cancer, some siblings expressed feelings such as anger and jealousy because the ill child received more attention. Others experienced depression, fear, anger, and isolation (Rosenberg et al, 2015;Yang, Mu, Sheng, Chen, & Hung, 2016). Feelings of uncertainty and anxiety were prevalent as well, especially during the time in which their family did not have an accurate diagnosis (D'Urso et al, 2017;Jenholt nolbris et al, 2014;Long, Marsland, Wright, & Hinds, 2015;Rosenberg et al, 2015;Salavati et al, 2014).…”
Section: An Array Of Emotional Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…As treatment continued for the child with cancer, some siblings expressed feelings such as anger and jealousy because the ill child received more attention. Others experienced depression, fear, anger, and isolation (Rosenberg et al, 2015;Yang, Mu, Sheng, Chen, & Hung, 2016). Feelings of uncertainty and anxiety were prevalent as well, especially during the time in which their family did not have an accurate diagnosis (D'Urso et al, 2017;Jenholt nolbris et al, 2014;Long, Marsland, Wright, & Hinds, 2015;Rosenberg et al, 2015;Salavati et al, 2014).…”
Section: An Array Of Emotional Changesmentioning
confidence: 99%
“…If mothers were sad and grieving, older siblings felt that they had to make their mothers as happy as possible. Some siblings attempted to establish new roles within their family, such as being present with the ill child and accompanying them to appointments in an attempt to maintain family normalcy (Yang et al, 2016). Younger siblings were less able empathize with their mothers, which led to confusion and fear in some of these children (Kamibeppu et al, 2015).…”
Section: An Array Of Emotional Changesmentioning
confidence: 99%
“…Approximately 300 000 children 0 to 19 years old are diagnosed with cancer worldwide each year . This affects the entire family in varying degrees, characterized by changes in individual and family life stories and routines both during treatment and in the years following . Parental attention is focused on the child with cancer, and the parental absence and loss of family routines causes the healthy sibling to experience a disintegration of life .…”
Section: Introductionmentioning
confidence: 99%
“…Parental attention is focused on the child with cancer, and the parental absence and loss of family routines causes the healthy sibling to experience a disintegration of life . Siblings report numerous unmet needs, such as lack of parental attention, related to the diagnosis and the new life situation . Several studies have investigated the impact of childhood cancer on the healthy sibling and found both positive and negative outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation